Integrating faith and psychology twelve psychologists tell their stories - Moriarty, Glendon (Downers Grove, Ill. : IVP Academic, 2010)
Twelve notable psychologists relate their journeys as Christians who entered the field of psychology. They provide personal reflections on their spiritual, personal and professional journeys of interrelating their faith and profession. --From publisher's description.
Surprised by grace : God's faithfulness in developing a Christian psychologist / Everett L. Worthington Jr. -- A search for belonging / L. Rebecca Propst -- My integration journey : reflections of a Christian psychologist and pastor / Siang-Yang Tan -- Journeying toward home / Mark R. McMinn -- Confessions of a tortoise : slow steps on the integration journey / M. Elizabeth Lewis Hall -- Practicing convicted civility / Mark A. Yarhouse -- Living the legacy : a letter to my students / Jennifer S. Ripley -- Honoring my tradition : particularity, practice and patience / Alvin C. Dueck -- Reluctant integration / J. Derek McNeil -- Faithful skepticism, curious faith / William L. Hathaway -- Setting one's face toward Jerusalem : a personal integration journey / Linda M. Wagener -- Integration and the Christian imagination / Cameron Lee.
Includes bibliographical references.
Description based on print version record.
Keywords: Christian biography; Psychologists -- Biography; Christianity -- Psychology; Psychology and religion; BIOGRAPHY & AUTOBIOGRAPHY / Religious; RELIGION / Philosophy; Electronic books